Influence of Abiotic Factors on the Incidence of Two Spotted Spider Mite, Tetranychus urticae Koch on Brinjal in Coastal Areas of Cuddalore District, Tamil Nadu, India - R., Athivarman; V., Sathyaseelan (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Brinjal, Solanum melongena L., is a native Indian vegetable belonging to the family Solanaceae. It was affected by various pests among which two spotted spider mite, Tetranychus urticae become a key pest. The influence of abiotic factors on the infestation of brinjal plant with mites was investigated during kharif-2022 (June to September) and rabi-2022-23 (November to March) seasons. T. urticae was found from the 24th to the 39th standard meteorological weeks (SMWs) in the kharif season and from the 47th to the 10th SMWs in the rabi season. The mite population increased gradually and reached to a peak in the second week of July with the population of 20.66 mites in kharif 2022 and second week of March with population of 21.80 mites in Rabi 2022 -23, respectively. The population of this pest started to be declined from the fourth week of July (10.13 mites /3 leaves) and also decreased to the level of 5.66 mites /3 leaves in the fourth week of August in kharif 2022. On the other hand, the population of mites started to be increased from the second week of February (15.06 mites /3 leaves) to the second week of March (21.80 mites/3 leaves) in rabi 2022-23. Generally, these results indicate that mites population gradually decreased with fall in the temperature during both seasons.